Novel anti-scaling and sterilizing integrated fracturing fluid and preparation method thereof

By using a combination scheme of PAAVV polymer with amide, sulfonic acid, phosphonic acid and quaternary phosphonium ionic liquid and montmorillonite, a thickener with high shear resistance was prepared, which solved the problem of existing fracturing fluid being volatile in high temperature and high shear conditions and the prone to wall penetration of scale inhibitor antibacterial agents, and achieved long-term anti-scaling and antibacterial properties.

CN119859521AActive Publication Date: 2025-04-22XIAN KAIERWEN PETROCHEMICAL AUXILIARY MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510314714.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-22
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

The existing fracturing fluid is prone to lose its stickiness under high temperature and high shear conditions, and scale inhibitors and antibacterial agents are prone to stick to walls and permeation after entering the formation, resulting in the lack of long-term anti-scaling and antibacterial properties.

Method used

The PAAVV polymer and montmorillonite combination scheme with amide, sulfonic acid, phosphonic acid and quaternary phosphonium ionic liquid is used to prepare a thickener with high shear resistance through quaternary ammonium salt intercalation and in-situ polymerization process. Through the optimization of formula and process, the organic combination of multiple functions such as anti-scaling, sterilization, thickening, sand carrying and rubber breaking is achieved.

Benefits of technology

It achieves good thickening performance under high shear conditions, improves sand carrying capacity, significantly improves anti-scaling and antibacterial properties, and ensures long-term use of fracturing fluid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859521A_ABST
    Figure CN119859521A_ABST
Patent Text Reader

Abstract

The invention discloses a novel anti-scaling and sterilizing integrated fracturing fluid and a preparation method thereof. The fracturing fluid comprises a thickening agent, a cross-linking agent, a surfactant, an anti-swelling agent, a gel breaker and water. The preparation method comprises the steps of montmorillonite treatment and montmorillonite in-situ polymerization. In order to cope with scaling and bacterial decay conditions in the actual water-based fracturing application process, the thickening agent adopts a scheme that a PAAVV polymer with amide, sulfonic acid, phosphonic acid and quaternary phosphonium salt ionic liquid is matched with montmorillonite, a sulfonic acid monomer provides salt resistance, a phosphonic acid monomer provides cross-linking point location and antibacterial property, and the PAAVV polymer and the montmorillonite are combined to form the thickening agent. The quaternary phosphonium salt ionic liquid monomer simultaneously provides extra thickening, antibacterial and dissolvability requirements, and the inter-layer acting force of the montmorillonite has the effect of transferring shearing force, so that the viscosity of the thickening agent is reduced slightly under long-time shearing and is ensured to be more than 35mPa. S; in conclusion, the fracturing fluid product disclosed by the invention realizes organic combination of multiple functions of scale prevention, sterilization, thickening, sand carrying, gel breaking and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydraulic fracturing fluid and its production technology, and in particular to a novel anti-scaling and sterilization integrated fracturing fluid and a preparation method thereof. Background Art

[0002] Fracturing fluid refers to a heterogeneous and unstable chemical system formed by a certain ratio of multiple additives. It is the working fluid used for fracturing oil and gas layers. Its main function is to transfer the high pressure formed by ground equipment to the formation, causing the formation to break and form cracks and transport proppant along the cracks.

[0003] The proportion of water-based fracturing fluid generally requires the following technical requirements: 1) Scale prevention: With the deepening of oil and gas field development, especially the exploitation of unconventional oil and gas resources such as shale gas, the composition of fracturing fluid return fluid is complex, containing a large amount of inorganic salts, organic matter and heavy metal ions. When flowing in equipment and pipelines, these substances are very easy to scale under certain conditions, causing serious corrosion and blockage to the equipment, affecting production efficiency and equipment service life. Therefore, scale prevention has become an important issue in the application of fracturing fluid.

[0004] 2) Antibacterial: The composition of oilfield flowback fluid is complex, containing a large amount of petroleum substances, heavy metal ions, chemical additives (such as demulsifiers, corrosion inhibitors, etc.) and microorganisms. The growth of microorganisms will cause the water quality of the flowback fluid to deteriorate, produce odor, and corrode pipelines and equipment. In addition, microorganisms aggregate to form biofilms, which will block the pores of the formation, reduce the permeability of the oil layer, and affect the subsequent production efficiency of the oil field.

[0005] 3) Shear resistance of thickener: The thickener in the drilling fluid has low shear resistance, which will cause the viscosity of the drilling fluid to drop sharply during the circulation process, especially when passing through high-speed shear areas such as the drill bit nozzle. The fluid cannot effectively carry rock cuttings, resulting in rock cuttings precipitation, which may clog the wellbore and affect the normal progress of the drilling operation. It may also cause instability of the well wall and cause accidents such as well collapse.

[0006] However, the amide thickeners in existing fracturing fluids are prone to lose viscosity under high temperature and high shear, and are prone to cause amide hydrolysis or degradation. At the same time, scale inhibitors and antibacterial agents are added in the form of small molecules or small particles mixed with thickeners, which are prone to sticking to the wall and penetrating into the formation, resulting in the fracturing fluid not having long-term anti-scale and antibacterial properties, which urgently needs to be improved. Summary of the invention

[0007] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a new anti-scaling and sterilization integrated fracturing fluid and a preparation method thereof.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention firstly proposes a novel anti-scaling and sterilizing integrated fracturing fluid, which comprises the following components in weight percentage: 0.5-0.8% of thickener, 0.3-0.4% of cross-linking agent, 0.4-0.6% of surfactant, 1-2% of anti-swelling agent, 0.01-0.05% of gel breaker, and the balance is water; In order to simultaneously deal with scaling and bacterial corrosion during the actual water-based fracturing application process, the thickener adopts a PAAVV polymer and montmorillonite solution with amide, sulfonic acid, phosphonic acid and quaternary phosphonium salt ionic liquids, while overcoming the high shear thickening effect. The specific preparation process is as follows: S1. Montmorillonite treatment: Quaternary ammonium salt intercalation: according to the cation exchange capacity of twice the sodium-montmorillonite (Na-MMT), a 20% by weight hexadecyltrimethylammonium bromide (CTAB) aqueous solution was prepared, added to a 3% by weight sodium-montmorillonite aqueous suspension, stirred at 500r / min, and kept in a water bath at 60°C for 4h. The precipitate obtained by the reaction was separated by centrifugation, filtered and washed until there was no bromide ion. The obtained product was dried at 60°C for 24h, ground and passed through a 200-mesh sieve to obtain organic montmorillonite A (OMMT); S2, montmorillonite in-situ polymerization: 1) Dry organic montmorillonite A and water are mixed and infiltrated in a weight ratio of 1:1, and then 4-vinylbenzyltributylphosphonium chloride (VBP-Bu) is added, dissolved at 60°C, and then ground to obtain a mixed slurry B; 2) Under nitrogen protection, acrylamide (AM), vinylphosphonic acid (VPA), and 2-acrylamido-2-methylpropanesulfonic acid (AMPS) are sequentially added into deionized water, wherein the amount of deionized water added is 3 times the total weight of acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid. Sodium hydroxide is added to adjust the pH of the system to 8-9, and a mixed slurry B is added. The ratio of the total weight of organic montmorillonite A to acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid in the mixed slurry B is 1:4. The molar ratio of 4-vinylbenzyltributylphosphonium chloride to acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid in the mixed slurry B is 0.3-0.8:10:1.6-2.3:0.9-1.2. Ammonium persulfate is added, wherein the amount of ammonium persulfate accounts for 1.5-2.5% of the total weight of the system. The mixture is reacted at 75°C for 5 hours to obtain a gel product C. 3) The gel product C was soaked in water for 10 h, ion was replaced, and the surface pH of the wet gel D was tested to be 7.5-8.5; 4) Using a colloid mill, wet gel D and deionized water were mixed in a weight ratio of 1:1, and deionized water was added five times while grinding to obtain a viscous colloid E with bubbles inside; 5) The viscous colloid E is hot-rolled into a film with a thickness of less than 10 mm, dried with hot air at 60°C, cut into pieces, and crushed to obtain a flake granular product, i.e., the finished thickener.

[0009] Preferably, the cross-linking agent is borax and EDTA compounded in a ratio of 2:1. Both borax and EDTA cross-link the phosphonic acid groups in the PAAVV polymer, wherein the amino group of EDTA has a strong connecting effect on the phosphonic acid groups, and EDTA has a coordination effect with calcium, magnesium, barium and other ions, further enhancing the anti-scaling effect.

[0010] Preferably, the surfactant is compounded by a sulfonate surfactant and a quaternary ammonium salt surfactant in a ratio of 4:1, and the quaternary ammonium salt surfactant includes any of cetyl trimethyl ammonium chloride (1631), polyquaternium-17, benzalkonium bromide or cetyl pyridinium bromide. The quaternary ammonium salt surfactant also has the function of an antibacterial agent, has good bactericidal, corrosion-inhibiting and clay-stabilizing properties, and is effective in preventing formation clay expansion and particle migration; Sulfonate surfactants are sodium alkylbenzene sulfonate (LAS), α-olefin sulfonate (AOS) or alkyl sulfonate (AS). They have good surface activity and the ability to reduce surface tension, wide sand carrying capacity, low filtration loss, high fracturing efficiency, and relatively low cost. They are used in water-based fracturing fluids.

[0011] Preferably, the anti-swelling agent is a small cationic anti-swelling agent HJZ-500 (Kaifeng Hengju Biotechnology Co., Ltd.) or a quaternary ammonium salt type clay stabilizer HJZ-500-1 (Kaifeng Hengju Biotechnology Co., Ltd.). The small cationic anti-swelling agent HJZ-500 is a compound of a cationic polymer and a variety of additives, and the quaternary ammonium salt type clay stabilizer HJZ-500-1 is a compound of a quaternary ammonium salt cationic polymer and a variety of additives. It is used to prevent the expansion and migration of reservoir particles such as shale, while increasing the degree of ionization of the system and increasing the anti-scaling effect.

[0012] Preferably, the breaker is an enzyme breaker or a redox breaker.

[0013] A more preferred solution is that the molar ratio of 4-vinylbenzyltributylphosphonium chloride to acrylamide, vinylphosphonic acid and 2-acrylamido-2-methylpropanesulfonic acid in the mixed slurry B is 0.5:10:2:1.

[0014] A more preferred solution is that the amount of ammonium persulfate in S2 accounts for 2% of the total weight of the system.

[0015] The present invention also proposes a method for preparing the aforementioned novel anti-scaling and sterilizing integrated fracturing fluid, comprising the following steps: mixing water, surfactant, anti-swelling agent, and gel breaker according to percentages, and stirring at high speed in a stirrer, and then slowly adding a thickener in a corresponding proportion, and after swelling is completed, adding a cross-linking agent, and finally obtaining the anti-scaling and sterilizing integrated fracturing fluid.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention first screens four monomers with amide, sulfonic acid, phosphonic acid and quaternary phosphonium salt ionic liquid through group screening for copolymerization. The amide monomer provides thickening performance and solubility requirements, the sulfonic acid monomer provides salt resistance, the phosphonic acid monomer provides cross-linking points (with borax) and antibacterial properties, and the quaternary phosphonium salt ionic liquid monomer provides additional thickening, antibacterial and solubility requirements. According to the polymerization effect and shear resistance test, the high shear debonding problem can be initially overcome; 2. At the same time, the present application also uses montmorillonite intercalated with long-chain quaternary ammonium salts, and utilizes the high permeability of ionic liquids to carry out polymer-montmorillonite in-situ polymerization. Degumming experiments have shown that the polymer phase and the inorganic phase are evenly distributed and cannot be separated. On the one hand, the polymer adhesion (or intercalation) improves the solubility of the montmorillonite, and on the other hand, the supporting force of the montmorillonite provides pressure resistance and the interlayer force has the function of transferring shear force, thereby ensuring that the viscosity of the thickener decreases less under long-term shearing and is guaranteed to be above 35mPa·s; 3. The novel anti-scaling and sterilizing integrated fracturing fluid of the present invention realizes the organic combination of multiple functions such as anti-scaling, sterilization, thickening, sand carrying and gel breaking by optimizing the formula and process, which is specifically embodied in: 1) High anti-scaling performance: Phosphonic acid groups and sulfonic acid groups are introduced into the thickener. These functional groups can form stable chelates with calcium, magnesium, barium and other ions in the formation, effectively preventing the formation of scale layers. The cross-linking agent is a compound of borax and EDTA. The amino group of EDTA has a strong connection effect on the phosphonic acid group. At the same time, EDTA can coordinate with metal ions to further improve the anti-scaling performance.

[0017] 2) High antibacterial property: The intercalated montmorillonite itself has a high ion adsorption capacity, especially for alkaline earth metal ions. The interlayer long-chain quaternary ammonium salt also has long-lasting antibacterial properties. The quaternary phosphonium salt ionic liquid monomer has high biological cell permeability and bactericidal effect. The surfactant is a compound of sulfonate and quaternary ammonium surfactants. The quaternary ammonium surfactant has good antibacterial properties and can effectively inhibit bacterial growth and reduce biological corrosion. 3) Enhanced thickening and sand carrying capacity: The thickener uses PAAVV polymer with amide, sulfonic acid, phosphonic acid and quaternary phosphonium salt ionic liquids, combined with the nano-enhancement effect of montmorillonite, which can maintain good thickening performance under high shear conditions and improve sand carrying capacity; The thickener prepared by the in-situ polymerization process of montmorillonite has higher mechanical stability and shear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the infrared spectrum of the thickener in the embodiment of the present invention; Figure 2 Graph showing the effect of concentration on the viscosity of a thickener aqueous solution in an embodiment of the present invention; Figure 3 This is a graph showing the effect of shear time on the viscosity of a thickener aqueous solution in an embodiment of the present invention; Figure 4 Graph showing the effect of temperature on the viscosity of a thickener aqueous solution in an embodiment of the present invention; Figure 5 Graph showing the effect of NaCl concentration on the viscosity of a thickener aqueous solution in an embodiment of the present invention; Figure 6 Graph showing the effect of CaCl2 concentration on the viscosity of the thickener aqueous solution in an embodiment of the present invention. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the existing known technologies. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0020] 1. Preparation of shear resistant thickener: 1. Preparation process: S1. Montmorillonite treatment: Quaternary ammonium salt intercalation: sodium montmorillonite, according to the cation exchange capacity (CEC) of twice that of sodium montmorillonite, a 25% by weight hexadecyl trimethyl ammonium bromide solution was prepared, added to a 5% by weight sodium montmorillonite suspension, stirred at 500 r / min, kept in a 60°C water bath for 4 hours, the precipitate obtained by the reaction was separated by centrifugation, filtered and washed until there was no bromide ion, the obtained product was dried at 60°C for 24 hours, ground and passed through a 200-mesh sieve to obtain organic montmorillonite A (OMMT); S2, in-situ polymerization The dried organic montmorillonite A and water were mixed and infiltrated in a weight ratio of 1:1, and then 4-vinylbenzyltributylphosphonium chloride was added, dissolved at 60°C, and then ground to obtain a mixed slurry B; Under nitrogen protection, acrylamide (AM), vinylphosphonic acid (VPA), and 2-acrylamido-2-methylpropanesulfonic acid (AMPS) are sequentially added into deionized water, wherein the amount of deionized water added is 3 times the total weight of acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid. Sodium hydroxide is added to adjust the pH of the system to 8-9, and a mixed slurry B is added. The ratio of the total weight of organic montmorillonite A to acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid in the mixed slurry B is 1:4 (the ratio is set according to the maximum solubility of montmorillonite), and the molar ratio of 4-vinylbenzyltributylphosphonium chloride (VBP-Bu) to acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid in the mixed slurry B is 0.3-0.8:10:1.6-2.3:0.9-1.2. An initiator ammonium persulfate (accounting for 1.5-2.5% of the total weight of the system) is added, and the reaction is carried out at 75°C for 5 hours to obtain a gel product C. The gel product C was treated three times by soaking in water for 10 h to replace ions, and the surface pH of the wet gel D was tested to be 7.5-8.5; The wet gel D and deionized water were mixed in a weight ratio of 1:1 by using a colloid mill. Deionized water was added five times while grinding to obtain a viscous colloid E with bubbles inside. The viscous colloid E is hot-rolled into a film with a thickness of less than 10 mm, dried with hot air at 60°C, cut into pieces and crushed to obtain a flake granular product, i.e., the finished thickener.

[0021] Source of reagents: Sodium montmorillonite (Na-MMT, 325 mesh), Hebei Leijiang New Materials Technology Co., Ltd.; Hexadecyltrimethylammonium bromide (CTAB, purity 99%), Shandong Guohua Chemical Co., Ltd.; Acrylamide (AM), anhydrous ethanol, sodium hydroxide, sodium chloride, calcium chloride, ammonium persulfate, all with a purity of AR, from Shanghai MacLean Biochemical Technology Co., Ltd.; Acrylamido-2-methylpropanesulfonic acid (AMPS), purity>99%, Shanghai Hongzhuang Chemical Technology Co., Ltd.; Vinylphosphonic acid (VPA), purity > 99%, Hubei Hongxin Ruiyu Fine Chemical Co., Ltd.; 4-vinylbenzyltributylphosphonium chloride (VBP-Bu ionic liquid, white powder, melts at 60°C to form ionic liquid), purity >99%, Shanghai Aladdin Biochemical Technology Co., Ltd.

[0022] According to the above steps, the thickener formula of each preparation example is as shown in Table 1: ; In order to verify the effects of various reagents and treatment procedures on thickening performance, anti-scaling and sterilization performance, the following thickeners for comparative preparation were prepared: Comparative Preparation Example 1: The components and steps are the same as those in Preparation Example 2, except that the sodium montmorillonite is not treated with quaternary ammonium salt intercalation.

[0023] Comparative Preparation Example 2: The components and steps are the same as those in Preparation Example 2, except that sodium montmorillonite is not used as the thickener. The specific process is as follows: The dried organic montmorillonite A and water were mixed and infiltrated in a weight ratio of 1:1, and then 4-vinylbenzyltributylphosphonium chloride was added, dissolved at 60°C, and then ground to obtain a mixed slurry B; Under nitrogen protection, acrylamide (AM), vinylphosphonic acid (VPA) and 2-acrylamido-2-methylpropanesulfonic acid (AMPS) are sequentially added into deionized water, the amount of deionized water added is 3 times the total weight of acrylamide, vinylphosphonic acid and 2-acrylamido-2-methylpropanesulfonic acid, sodium hydroxide is added to adjust the pH of the system to 8-9, 4-vinylbenzyltributylphosphonium chloride (VBP-Bu) is added, and initiator ammonium persulfate (accounting for 2% of the total weight of the system) is added, and the reaction is carried out at 75°C for 5h to obtain a gel product, which is then soaked in water, rinsed, filtered and dried to obtain a granular product, i.e., the finished thickener.

[0024] Comparative Preparation Example 3: The components and steps are the same as those in Preparation Example 2, except that the wet gel D is directly dried and crushed. The specific process is as follows: S1. Montmorillonite treatment: Quaternary ammonium salt intercalation: sodium montmorillonite, according to the cation exchange capacity (CEC) of twice that of sodium montmorillonite, a 25% by weight hexadecyl trimethyl ammonium bromide solution was prepared, added to a 5% by weight sodium montmorillonite suspension, stirred at 500 r / min, kept in a 60°C water bath for 4 hours, the precipitate obtained by the reaction was separated by centrifugation, filtered and washed until there was no bromide ion, the obtained product was dried at 60°C for 24 hours, ground and passed through a 200-mesh sieve to obtain organic montmorillonite A (OMMT); S2, in-situ polymerization The dried organic montmorillonite A and water were mixed and infiltrated in a weight ratio of 1:1, and then 4-vinylbenzyltributylphosphonium chloride was added, dissolved at 60°C, and then ground to obtain a mixed slurry B; Under nitrogen protection, acrylamide (AM), vinylphosphonic acid (VPA), and 2-acrylamido-2-methylpropanesulfonic acid (AMPS) are sequentially added into deionized water, wherein the amount of deionized water added is 3 times the total weight of acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid. Sodium hydroxide is added to adjust the pH of the system to 8-9, and a mixed slurry B is added. The ratio of the total weight of organic montmorillonite A to acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid in the mixed slurry B is 1:4 (the ratio is set according to the maximum solubility of montmorillonite), and the molar ratio of 4-vinylbenzyltributylphosphonium chloride (VBP-Bu) to acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid in the mixed slurry B is 0.3-0.8:10:1.6-2.3:0.9-1.2. An initiator ammonium persulfate (accounting for 2% of the total weight of the system) is added, and the reaction is carried out at 75°C for 5 hours to obtain a gel product C. The gel product C was soaked in water for 10 hours, and the ions were replaced for 3 times. The surface pH of the wet gel D was tested to be 7.5-8.5. The wet gel D was dried and crushed to obtain the finished thickener.

[0025] 2. Detection of thickener: 1) Mixed traits: The finished thickener was prepared as a 5% aqueous solution by mass, which did not settle within 10 days, while the settling time of the sodium montmorillonite suspension and the organic montmorillonite A suspension with the same weight was 18 minutes and 70 minutes respectively; Degumming experiment: The finished thickener was prepared into a 0.5% aqueous solution by mass, filtered through a 150-mesh sieve, and rinsed with deionized water three times. The filter cake obtained was still in a gel state with particles inside. The particles could not be separated from the transparent colloid, indicating that the polymer network was well entangled with the montmorillonite matrix and would not fall off.

[0026] 2) FT-IR characterization: The infrared spectrum of the sample was measured by KBr tablet method using WQF-520 Fourier infrared spectrometer, and infrared detection was performed on sodium montmorillonite, organic montmorillonite A and finished thickener respectively; Reference Figure 1 The infrared of the bulk of sodium montmorillonite (MMT) and the quaternary ammonium salt in organic montmorillonite A (OMMT) are both reflected. -1 The strong absorption band at 2928cm is the Si-O-Si skeleton vibration, which is the characteristic absorption peak of montmorillonite. -1 ,2854cm -1 ,1469.6cm -1 The absorption peak of -CH2 of quaternary ammonium salt is at the bottom, while the layered silicate skeleton of montmorillonite has not changed, indicating that the quaternary ammonium salt is indeed embedded in the interlayer of montmorillonite. PAAVV-MMT (PMMT): 3430cm -1 and 3210cm -1 It is the characteristic peak of amide group. The S=O bond in AMPS is at 1184cm -1 and 1043cm -1 The P=O bond is at 1250-1300cm -1 The C=O of the amide group is at 1660-1680cm -1 The absorption peaks will still be reflected in the infrared spectrum, but the position and intensity of the absorption peaks may change due to the interference of the inorganic phase of montmorillonite.

[0027] 3) Performance evaluation of polymer PAAVV ① Thickening performance test: The thickeners in Preparation Examples 1-5 were used to prepare aqueous solutions of polymer PAAVV with different mass fractions. The apparent viscosity was measured by a six-speed rotary viscometer at room temperature (25°C) and 170s -7 Measured at shear rate, see Figure 2 ; ② Cross-linking test: Prepare PAAVV polymer solution, control the mass fraction to 0.5%, after fully dissolved, adjust the pH value to 6 with 3wt% dilute hydrochloric acid, prepare 0.4% mass fraction of borax aqueous solution, according to the volume ratio of PAAVV polymer solution to borax aqueous solution of 100:5, add borax aqueous solution to PAAVV polymer solution, stir rapidly with a glass rod at 30°C, record the reaction time (stopwatch reading) when the cross-linked product can be hung and not agglomerated (proving that the cross-linking effect is good), the cross-linking time of the thickener of Preparation Example 1-5 and Comparative Preparation Example 1-3 is shown in Table 2 below: ; Among them, the cross-linking time of Comparative Preparation Example 1 is shorter, but the particle aggregation visible to the naked eye is more obvious. A small amount of particles are deposited at the bottom of the PAAVV polymer solution after being placed for 3 days. The product of Comparative Preparation Example 3 has not undergone grinding and pre-shearing treatment. When preparing the aqueous solution, the dissolution and diffusion rate is slower than that of Preparation Example 2. The PAAVV polymer solution is placed for 10 days, and there are suspended aggregates inside the solution. The grinding process of the rubber mill is conducive to the uniform distribution of the polymer phase and the montmorillonite matrix.

[0028] ③ Shear resistance test: Taking Preparation Example 2 and Comparative Preparation Example 2 as examples, the thickener was prepared into a PAAVV polymer solution with a controlled mass fraction of 0.5%. -7 At different shear rates, the apparent viscosity was measured at different shear times. Figure 3 .

[0029] ④ Temperature resistance test: Prepare PAAVV polymer solution, control the mass fraction to 0.5%, use a six-speed rotation viscometer to test the apparent viscosity of the solution at different temperatures, and control the shear rate at 170s -1 ,See Figure 4 .

[0030] ⑤ Salt resistance test: Taking Preparation Example 2 and Comparative Preparation Example 2 as examples, a polymer PAAVV solution was prepared, and its mass fraction was controlled to be 0.5%. NaCl or CaCl2 was continuously added, and the change of the apparent viscosity of the solution was tested with a six-speed rotation viscometer, where the conditions were controlled at room temperature (25°C) and 170s -1 The shear rates are shown in Figure 5 and Figure 6 , and the concentration in the figure is the proportion of NaCl or CaCl2 in the solution system (wt%).

[0031] 3. Thickener formula screening process: 1) According to Figure 2 As well as the degree of crosslinking of the thickeners obtained in Preparation Examples 1-5, the viscosity of the thickeners increased slightly with the increase of VBP-Bu (comparison with Preparation Examples 1-3); 2) As the amount of ammonium persulfate increases, the thickener with a higher molecular weight (Preparation Example 4) has a better viscosity-increasing effect at a low concentration, while the thickener with a smaller molecular weight (Preparation Example 5) has a better viscosity-increasing effect at a high concentration; 3) According to Figure 4 , Preparation Example 1-5 still maintains about 70mPa·s at high temperature, which is suitable for use as a high temperature resistant fracturing fluid; 4) According to Figure 5 and Figure 6 , the salt resistance of the thickener is significantly improved by adding montmorillonite, and the apparent viscosity is still above 35mPa·s in high salt concentration; 5) According to Figure 3 Based on the above data, the addition of montmorillonite significantly improves the shear resistance of the thickener. In addition, according to the usage of existing thickeners in fracturing fluids and the quantity requirements of amides or ions, Preparation Example 2 is temporarily determined to be the optimal formula.

[0032] 2. Preparation of fracturing fluid: Thickener: taken from Preparation Examples 1-5 and Comparative Preparation Examples 1-3, used for comparison.

[0033] Cross-linking agent: Borax (2000 mesh, Langfang Pengcai Fine Chemical Co., Ltd.) and EDTA (AR, Langfang Pengcai Fine Chemical Co., Ltd.) are compounded in a ratio of 2:1. Both borax and EDTA cross-link the phosphonic acid groups in the PAAVV polymer. The amino group of EDTA has a strong connection effect on the phosphonic acid group, and EDTA has a coordination effect with calcium, magnesium, barium and other ions, further improving the anti-scaling effect; Surfactant: Sulfonate surfactant and quaternary ammonium salt surfactant are compounded in a ratio of 4:1; Quaternary ammonium surfactants: hexadecyltrimethylammonium chloride (1631), polyquaternium-17, benzalkonium bromide or hexadecylpyridinium bromide, which have antimicrobial properties, good bactericidal, corrosion-inhibiting and clay-stabilizing properties, and are effective in preventing clay expansion and particle migration in formations; Sulfonate surfactants: sodium alkylbenzene sulfonate (LAS), α-olefin sulfonate (AOS) or alkyl sulfonate (AS), have good surface activity and ability to reduce surface tension, wide range of sand carrying capacity, low filtration loss, high fracturing efficiency, relatively low cost, and are used in water-based fracturing fluids.

[0034] Anti-swelling agent: small cationic anti-swelling agent HJZ-500 (Kaifeng Hengju Biotechnology Co., Ltd.) or quaternary ammonium salt clay stabilizer HJZ-500-1 (Kaifeng Hengju Biotechnology Co., Ltd.). Small cationic anti-swelling agent HJZ-500 is a compound of cationic polymer and various additives, and quaternary ammonium salt clay stabilizer HJZ-500-1 is a compound of quaternary ammonium salt cationic polymer and various additives. It is used to prevent the expansion and migration of shale and other reservoir particles, while increasing the degree of system ionization and the anti-scaling effect. Gel breakers: enzyme gel breakers (petroleum fracturing gel breakers, enzyme activity 50,000 u, Nantong Yingruida Biotechnology Co., Ltd.), redox gel breakers (ammonium persulfate capsule gel breakers, Dongying Yiming Chemical Co., Ltd.).

[0035] The fracturing fluid formula used in the specific examples and comparative examples is as shown in Table 3: ; Scale inhibition test: prepare simulated aqueous solutions with solute weight percentages of 1% potassium chloride, 1.5% sodium chloride, 0.5% magnesium chloride, and 0.2% calcium chloride, respectively. The solvent is the flowback fluid from the 7# hydraulic fracturing oil production well in Haishiwan, Gansu (wherein the water weight content is 89.1wt%, and the sulfate content is 1.2wt%). Mix various fracturing fluids into the simulated aqueous solution. The weight ratio of fracturing fluid to simulated aqueous solution is 1:9. Observe the metal content m1 in the weight of the sediment (after drying), the metal content m2 in the solute, and the scale inhibition rate θ= (m2-m1) / m2, calculated as CaSO4; Antibacterial test: The flowback fluid from the 7# hydraulic fracturing oil well in Haishiwan, Gansu Province (with a water content of 89.1wt% and a sulfate content of 1.2wt%) was measured by a colony counter (Interscience Scan100, France) to determine the concentration of the bacterial solution. The content of Flavobacterium C was 7.5×10 5 / ml, which is a blank standard solution, and the fracturing fluids of Examples 1-5 and Comparative Examples 1-5 are added to the flowback fluid respectively to form the test solution; The blank standard solution and each test solution were cultured at 37°C for 7 days, and then the stock solution was diluted 100 times in sequence, and the number of colonies in the plate was measured. The bacterial concentration was calculated according to the formula: bacterial concentration ( / mL) = number of bacteria visually observed in the counting room × 10 4 × dilution factor, calculate the bacterial concentration of each test solution as S n , the bacterial concentration of the test solution is S0, and the bactericidal rate τ is calculated as (S n -S0) / S0.

[0036] See Table 4 below for specific data: ; Combined with Table 4 Figure 2-6 It can be seen that the comparison of Examples 1-5 proves that the increase of VPA phosphonic acid content is conducive to the increase of antibacterial properties, which meets the antibacterial requirements of polyphosphonic acid. It also proves that the solution of using phosphonic acid instead of existing carboxylic acid as a cross-linking point (cross-linking with borax) is feasible.

[0037] Comparing Comparative Examples 1 and 3 with Example 2, the amount of quaternary ammonium salt in the system is reduced, which reduces the bactericidal ability, while montmorillonite improves the ion inclusion capacity of the effective components of the fracturing fluid, and is particularly suitable for oil wells with high salt concentrations.

[0038] Comparing Comparative Example 2 with Example 2, the pre-grinding treatment is beneficial to the uniform distribution of montmorillonite and the polymer phase, and further improves the ion adsorption capacity.

[0039] Comparing Comparative Examples 4-5 with Example 2, a trace amount of EDTA further enhances the anti-scaling function, and a trace amount of hexadecyltrimethylammonium chloride further enhances the sterilization rate.

[0040] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A novel anti-scaling and sterilizing integrated fracturing fluid, characterized in that: The composition comprises the following components in weight percentage: 0.5-0.8% of thickener, 0.3-0.4% of cross-linking agent, 0.4-0.6% of surfactant, 1-2% of anti-swelling agent, 0.01-0.05% of debonding agent, and the balance is water; The preparation process of the thickener is as follows: S1. Montmorillonite treatment: Quaternary ammonium salt intercalation: according to the cation exchange capacity of twice the sodium montmorillonite, a 20% by weight aqueous solution of hexadecyltrimethylammonium bromide was prepared, added to a 3% by weight aqueous suspension of sodium montmorillonite, stirred at 500 r / min, kept warm in a 60°C water bath for 4 hours, the precipitate obtained by the reaction was separated by centrifugation, filtered and washed until there was no bromide ion, the obtained product was dried at 60°C for 24 hours, ground and passed through a 200-mesh sieve to obtain organic montmorillonite A; S2, montmorillonite in-situ polymerization: 1) Mix and infiltrate dried organic montmorillonite A and water in a weight ratio of 1:1, then add 4-vinylbenzyltributylphosphonium chloride, dissolve at 60°C, and grind to obtain a mixed slurry B; 2) Under nitrogen protection, acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid are sequentially added into deionized water, wherein the amount of deionized water added is 3 times the total weight of acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid, sodium hydroxide is added to adjust the pH of the system to 8-9, and mixed slurry B is added, wherein the ratio of the total weight of organic montmorillonite A to acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid in the mixed slurry B is 1:4, and the molar ratio of 4-vinylbenzyltributylphosphonium chloride to acrylamide, vinylphosphonic acid, and 2-acrylamido-2-methylpropanesulfonic acid in the mixed slurry B is 0.3-0.8:10:1.6-2.3:0.9-1.2, and ammonium persulfate is added, wherein the amount of ammonium persulfate accounts for 1.5-2.5% of the total weight of the system, and the reaction is carried out at 75°C for 5 hours to obtain a gel product C; 3) The gel product C was soaked in water for 10 h, ion was replaced, and the surface pH of the wet gel D was tested to be 7.5-8.5; 4) Using a colloid mill, wet gel D and deionized water were mixed in a weight ratio of 1:1, and deionized water was added five times while grinding to obtain a viscous colloid E with bubbles inside; 5) The viscous colloid E is hot-rolled into a film with a thickness of less than 10 mm, dried with hot air at 60°C, cut into pieces, and crushed to obtain a flake granular product, i.e., the finished thickener.

2. A novel anti-scaling and sterilizing integrated fracturing fluid according to claim 1, characterized in that: The cross-linking agent is prepared by mixing borax and EDTA in a ratio of 2:

1.

3. A novel anti-scaling and sterilizing integrated fracturing fluid according to claim 1, characterized in that: The surfactant is prepared by compounding a sulfonate surfactant and a quaternary ammonium salt surfactant in a ratio of 4:1, and the quaternary ammonium salt surfactant includes any of cetyltrimethylammonium chloride, polyquaternium-17, benzalkonium bromide or cetylpyridinium bromide; The sulfonate surfactant is sodium alkylbenzene sulfonate, α-olefin sulfonate or alkyl sulfonate.

4. The novel anti-scaling and sterilizing integrated fracturing fluid according to claim 1, characterized in that: The anti-swelling agent is a small cationic anti-swelling agent HJZ-500 or a quaternary ammonium salt type clay stabilizer HJZ-500-1.

5. The novel anti-scaling and sterilizing integrated fracturing fluid according to claim 1, characterized in that: The breaker is an enzyme breaker or a redox breaker.

6. The novel anti-scaling and sterilizing integrated fracturing fluid according to claim 1, characterized in that: The molar ratio of 4-vinylbenzyltributylphosphonium chloride to acrylamide, vinylphosphonic acid and 2-acrylamido-2-methylpropanesulfonic acid in the mixed slurry B is 0.5:10:2:

1.

7. The novel anti-scaling and sterilizing integrated fracturing fluid according to claim 1, characterized in that: The amount of ammonium persulfate in S2 accounts for 2% of the total weight of the system in 2).

8. A method for preparing a novel anti-scaling and sterilizing integrated fracturing fluid according to any one of claims 1 to 7, characterized in that: The following steps are involved: Water, surfactant, anti-swelling agent and degelling agent are mixed according to percentage and stirred at high speed in a stirrer, and then a corresponding proportion of thickener is slowly added. After swelling is completed, a cross-linking agent is added to finally obtain an anti-scaling and sterilization integrated fracturing fluid.

Citation Information

Patent Citations

  • Quaternary ammonium cation and quaternary phosphonium cation-containing modified clay, its preparation and application

    CN102816461A

  • Preparation method of polyacrylamide nano composite fracturing fluid

    CN104109525A

  • Preparation method of scale prevention, resistance reduction and thickening integrated fracturing emulsion

    CN115322283A

  • Antibacterial polyethylene pipe and preparation method thereof

    CN116496562A

  • Fracturing fluid drag reducer and preparation process thereof

    CN116656335A